The conventions of the research that informs Australian cultural policy about writing and publishing - Henningsgaard, Per (DarntonWatch, 2020)
The public funding of the arts in Australia is a topic that has received considerable attention by researchers (Throsby, 2007). More specifically, the evolution of policy towards the book industry in Australia has been the subject of research for at least the last couple decades (Throsby, 2018). This type of research is meant to evaluate Australian cultural policy about writing and publishing, but of course there is also research that directly informs this policy—either shaping the terms of its funding or justifying its continued existence. Some of the more remarkable recent examples of the latter type of research include the ‘Visiting International Publishers (VIP) Program: Longitudinal Evaluation 2011–2016’, ‘The Australian Book Industry: Authors, Publishers, and Readers in a Time of Change’, and the ‘WA Writing Sector Review: Final Report and Recommendations’. Some examples of this type of research are commissioned specifically to inform cultural policy, while other examples have different origin stories but are later leveraged for the same purpose. Some examples are produced by academic researchers, while others are produced by the cultural policymakers themselves. Despite this diversity, there are certain established (usually unspoken) conventions to the research that informs Australian cultural policy about writing and publishing, and these conventions structure the operation of the publishing industry by influencing the inner and outer workings of the field.